2021
DOI: 10.1007/s11024-021-09441-w
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Incentives for International Publications on Research Cultures in Chinese Humanities and Social Sciences

Abstract: Incentives for improving research productivity at universities prevail in global academia. However, the rationale, methodology, and impact of such incentives and consequent evaluation regimes are in need of scrutinization. This paper explores the influences of financial and career-related publishing incentive schemes on research cultures. It draws on an analysis of 75 interviews with academics, senior university administrators, and journal editors from China, a country that has seen widespread reliance on inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…In addition, the conventional incentives for publications scheme at various universities worldwide favor research articles over other forms of published documents in academia. For example, the study by Xu 20 reported that the practice of granting incentives for the publication of articles in international journals is widespread in China. Similar reports have highlighted the existence of the practice in many other countries such as the United States, Germany, Denmark, South Africa, and Malaysia, among others.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the conventional incentives for publications scheme at various universities worldwide favor research articles over other forms of published documents in academia. For example, the study by Xu 20 reported that the practice of granting incentives for the publication of articles in international journals is widespread in China. Similar reports have highlighted the existence of the practice in many other countries such as the United States, Germany, Denmark, South Africa, and Malaysia, among others.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, scientometric evaluative techniques have become popular in universities' human resources management, including in decisions concerning academic staff appointments, promotions, and tenure (Smith, Crookes, & Crookes, 2013). This evaluation method effectively stimulates academics to publish in high-impact journals; however, it has drawbacks, particularly for the humanities and social sciences (HSS) and in non-English-speaking countries (Xu et al, 2021). The high priority given to international journals also directs academics' attention to topics with international relevance, thereby discouraging both research on local issues and publishing findings in national journals (Li & Li, 2021;Mathies et al, 2020).…”
Section: Effect On Research Productivity and Publication Patternsmentioning
confidence: 99%
“…To be included in this project, Chinese universities are particularly eager for high numbers of publications in international and national journals indexed by Science Citation Index (SCI), Social Sciences Citation Index (SSCI), Chinese Science Citation Index (CSCI), and Chinese Social Sciences Citation Index (CSSCI), especially those with high impact factors ( Zhang and Sivertsen, 2020 ; Li and Xue, 2021 ). Despite recent national policies has been introduced to lessen the emphasis on SCI/SSCI publications but more emphasis on the importance of publications in domestic journals, such as CSSCI (Chinese Social Sciences Citation Index), many universities in China still use the SSCI- or SCI-related metrics as an important basis (if not only) for research evaluations, for its convenience and apparent objectivity ( Xu X. et al, 2021 ). As for the national/provincial grants-rewarding system in China, there has long been a systemic bias toward the natural sciences and technology compared to humanities and social sciences.…”
Section: Background Literaturementioning
confidence: 99%